Inspection & testing (Guidance note (Institution of Engineering and Technology))
A guide to electrical inspection and testing. It is part of a series of manuals designed to amplify the particular requirements of a part of the 16th Edition Wiring Regulations. Each of the guides is extensively cross-referenced to the Regulations thus providing easy access. Some Guidance Notes contain information not included in the 16th Edition but which was included in earlier editions of the IEE Wiring Regulations. All the guides have been updated to align with BS 7671:2001.